2022
DOI: 10.3390/vaccines10071131
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Antibody Response against Mild-to-Moderate Breakthrough COVID-19 in Home Isolation Setting in Thailand

Abstract: Background: In December 2021, Omicron replaced Delta as the dominant coronavirus disease 2019 (COVID-19) variant in Thailand. Both variants embody diverse epidemiological trends and immunogenicity. We investigated whether Delta and Omicron patients’ biological and clinical characteristics and immunogenicity differed post-COVID-19 infection. Methods: This retrospective cohort study investigated the clinical outcomes and laboratory data of 5181 patients with mild-to-moderate COVID-19 (Delta, 2704; Omicron, 2477)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Analyses considered viral load for comparisons of Ct values by vaccine exposure groups and self-reported symptoms as previously described. 6…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Analyses considered viral load for comparisons of Ct values by vaccine exposure groups and self-reported symptoms as previously described. 6…”
Section: Methodsmentioning
confidence: 99%
“…06S600), SARS-CoV-2 IgG II Quant for use with ARCHITECT; Abbott Laboratories, USA) as described previously. 6 This assay linearly measures the antibody level between 21.0 - 80,000.0 arbitrary unit (AU)/mL, which was converted later to WHO International Standard concentration as binding antibody unit per mL (BAU/mL) following the equation provided by the manufacturer (BAU/mL = 0.142 x AU/mL). The level greater or equal to the cutoff value of 50 AU/mL or 7.1 BAU/mL was defined as seropositive.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our "home isolation" (HI) strategy and in vitro and in vivo studies demonstrated that the Omicron variant replicated well in the upper respiratory tract but was poorly involved in the lower respiratory tract [18], leading to higher transmissibility than the Delta variant. A body of evidence shows that breakthrough infections have still occurred since the Delta variant wave, increasing total daily confirmed cases, and that primary immunization with the current available approved vaccines provides limited protection against symptomatic disease due to the Omicron variant, so that a booster shot is indispensable [19,20]. Still, vaccination and prior infection have been documented to reduce COVID-19 transmission during an Omicron-predominant period, and additional doses of updated vaccination (bivalent vaccines) led to greater reductions in infectiousness, thereby providing additional protection against symptomatic new SARS-CoV-2 variant infection [21,22].…”
Section: Introductionmentioning
confidence: 99%